On-the-job training demands of nursing managers in China: a scoping review - Jing-Jing CHEN; Yi-Juan CHENG; Zhong-Lan CHEN (Yixue xinzhi zazhi)
Objective Analyze the demand for on-the-job training of nursing managers in China.Methods CNKI, WanFang Data, VIP database, PubMed and Web of Science were electronically searched from August 1, 2005 to February 29, 2020. Cross-sectional studies on training demands of Chinese nursing managers covering training methods, training duration, training content and trainers were collected.Results A total of 23 studies were included, involving a total of 21,495 subjects. The research results show that clinical field teaching and follow-through, class training, case discussions and seminars are the most preferred training methods for nursing managers; they favor training events of about 1 week’s duration; and select both domestic and foreign first-line nursing management experts. The system of training content is designed using four modules: nursing management, human resources management, financial management, laws and regulations specific to the subject of the course. Nursing quality, nursing safety, performance management, team building and interpersonal communication are identified as the most needed topics.Conclusion It is suggested that future nursing management personnel training, should be designed with the training content and organization selected according to training demands of nursing managers, so as to ensure the delivery of higher quality training.